2022
DOI: 10.1111/anec.12994
|View full text |Cite
|
Sign up to set email alerts
|

Steep repolarization time gradients in pig hearts cause distinct changes in composite electrocardiographic T‐wave parameters

Abstract: Background The T wave of the electrocardiogram (ECG) reflects ventricular repolarization. Repolarization heterogeneity is associated with reentrant arrhythmias. Several T‐wave markers (including QT interval) have been associated with ventricular arrhythmias, but studies linking such markers to underlying local repolarization time (RT) inhomogeneities are lacking. We aimed to investigate the relation of several T‐wave markers to controlled drug‐induced regional RT gradients in intact pig hearts. Methods Repolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We here demonstrate that blebbistatin alters cardiac electrophysiology in a time-dependent manner when applied the Frontiers in Physiology frontiersin.org commonly used concentration of 10 µM and did not at the lower concentration of 1 µM. Strikingly, previous research highlighted that blebbistatin can precipitate, blocking myocardial microvasculature and thereby inducing ischaemia and metabolic changes (Swift et al, 2012). In addition, a prolonging effect of blebbistatin on repolarization has been described in isolated hearts from rabbit (Brack et al, 2013) and pig (Lee et al, 2019), although other studies report no impact of blebbistatin on AP parameters (Fedorov et al, 2007;Marchant, et al, 2022).…”
Section: Blebbistatin Time Effectmentioning
confidence: 54%
See 1 more Smart Citation
“…We here demonstrate that blebbistatin alters cardiac electrophysiology in a time-dependent manner when applied the Frontiers in Physiology frontiersin.org commonly used concentration of 10 µM and did not at the lower concentration of 1 µM. Strikingly, previous research highlighted that blebbistatin can precipitate, blocking myocardial microvasculature and thereby inducing ischaemia and metabolic changes (Swift et al, 2012). In addition, a prolonging effect of blebbistatin on repolarization has been described in isolated hearts from rabbit (Brack et al, 2013) and pig (Lee et al, 2019), although other studies report no impact of blebbistatin on AP parameters (Fedorov et al, 2007;Marchant, et al, 2022).…”
Section: Blebbistatin Time Effectmentioning
confidence: 54%
“…The largest gradient in APRD 90 was induced by illuminating the apex and resulted in a gradient of ~15 ms in APRD 90 between the apical and basal regions of the heart. Previous studies in a porcine model, in which RT gradients were induced by the infusion of drugs specific coronary arteries reported significantly larger RT gradients, with average gradients achieved reaching around 80 ms (Rivaud et al, 2021;van der Waal et al, 2022). However, total repolarization is also considerably longer in porcine hearts as compared to murine hearts.…”
Section: Sub-threshold Induced Repolarization Gradients: Relevance Fo...mentioning
confidence: 85%
“…This is relevant to the clinical translatability because the present study showed that the antiarrhythmic effects of ranolazine were dependent on the spatial extent of the repolarisation heterogeneity. Therefore, understanding of the role of repolarisation heterogeneity in arrhythmic risk, and pharmacologic modulation by late Na + block, may be improved by overcoming the significant difficulties in measuring repolarisation heterogeneity in vivo ( Sahu et al, 2000 ; van der Waal et al, 2022 ). Correspondingly, although we identified decreases of the JT c with ranolazine in some leads and this is consistent with the effects of disopyramide in HCM ( Maurizi et al, 2023 ), measures of repolarisation heterogeneity were not addressed due to large numbers of lead exclusions ( Sahu et al, 2000 ).…”
Section: Limitationsmentioning
confidence: 99%